Campylobacter in farm animals - John, Amy (2011)
Campylobaeter jejuni and C. coli are common causes of acute gastroenteritis in humans that are also associated with Guillain Barre and Miller Fisher syndrome. Poultry and other farm animals are the major sources of these pathogens. In this thesis it was demonstrated that hydrogen has the potential to act as an antioxidant to reduce oxidative stress caused during the growth of C. jejuni HPC5 when grown in a gas replacement jar. Growth in the absence of hydrogen in a modular atmosphere controlled system (MACS) was characterised by an intiallag that could be overcome by adding an antioxidant reagent FBP (10% ferrous sulphate, sodium pyruvate and sodium metabisulphite). Transcriptomic studies revealed that growth in the absence of hydrogen resulted in significant increases in the expression of superoxide dismutase, thiol peroxidase and ribosomal proteins. Transcriptomic studies were performed on the variants of C. jejuni HPC5 where bacteriophage predation had provoked intragenornic recombination to create second generation resistant types that are inefficient colonisers of chickens but revert to efficient colonisers and bacteriophage sensitivity when reintroduced into chickens to create third generation variants. The second generation variants were temperature sensitive, exhibited increased expression ofprophage Mu genes and low expression of motility associated genes. In contrast third generation variants showed an increase in the expression of the motility genes, an increase in the genes associated with the putative bacteriophage immunity factor CRISPR and reduced expression of Mu genes. Studies conducted on pigs demonstrated that a single pig can be colonised by campylobacters belonging to multiple genotypes and species. Comparative genomic hybridisation (CGH) of C. coli and C. jejuni isolated from the intestines of a single pig demonstrated these isolates shared plasmid and chromosomal encoded genes, and therefore may have undergone inter-species gene transfer due to cohabitation of a common intestinal niche. The aim of this thesis is to genotypically characterise Campylobaeter strains from chicken and pig in ideal atmospheric conditions. Our hypothesis is that Campylobacter can be grown in vitro both in gas replacement jar (ORJ) and in MACS and the molecular characterisation by transcriptomic analysis and CGH of the strains will be ideal in an atmospheric condition which is stress free.